Diseño, construcción y control de una máquina de inyección de plásticos reciclables. - Coraizaca Chuqui, Edison Gustavo (2023)
The following project took on the design, construction and control of a vertical injection machine with its capacity of 50 grams, using as raw material the thermoplastic polymer known as Polyethylene Terephthalate (PET), due to its availability in the world. Regarding the development, the size and price were taken into account, starting from the machines types and, selecting a suitable option for the design. The design began with the selection of injection parameters, mechanical, electrical, electropneumatical and control wise elements, followed by the mechanical elements calculation involving material resistance concepts, engineering related materials, mechanical design and, heat transfer, moreover, pneumatic, electronic and industrial control concepts were used for the control and power elements. The machine possesses an injection unit, control unit, potency unit and closing unit. Both the injection and closing unit are activated by pneumatic cylinders. The control unit has as a primary component a microcontroller Atmega 328, additionally the control plate was designed through the software Eagle which allows the valve control and the acquirement of sensor and push buttons signals. In the functionality testing phase, the plastification time was registered which consists in a value of 180 seconds, whereas the injection and support is 15 s, and the solidification is 20 s, with a pressure of 80-90 psi, an injection temperature in the barrel of 320 °C and 60 °C on the mold. The construction price was evaluated and the plans were done. Key words: Injection machine, thermoplastic injection, Polyethylene Terephthalate (PET), recyclable plastics.